2020
DOI: 10.1002/hlca.202000038
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Biology of the Clinically Used Macrolactone Antibiotic Fidaxomicin

Abstract: Fidaxomicin (1, lipiarmycin A3, clostomicin B1, tiacumicin B) constitutes a glycosylated 18-membered macrolactone and is a natural product isolated from various soil bacteria. Since 2011, fidaxomicin is a marketed antibiotic for the treatment of intestine infections caused by C. difficile in the clinic. Its promising in vitro antibacterial properties against resistant S. aureus and M. tuberculosis continue to attract interest. This review article describes the early history of the antibiotic fidaxomicin and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…The reason for our choice lies in the long and intriguing history of this natural product. Indeed, this macrolide returned to the fore as demonstrated by the great number of scientific studies that were published in very recent years [ 143 , 144 , 145 ].…”
Section: Antibiotics From Actinomycetes : From Isolation To Chemical Characterization Total Synthesis and Industrial Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for our choice lies in the long and intriguing history of this natural product. Indeed, this macrolide returned to the fore as demonstrated by the great number of scientific studies that were published in very recent years [ 143 , 144 , 145 ].…”
Section: Antibiotics From Actinomycetes : From Isolation To Chemical Characterization Total Synthesis and Industrial Pmentioning
confidence: 99%
“…Although the debate on the lipiarmycin structural determination is now closed, the studies on the synthesis of this antibiotic have increased, fostered by renewed interest for the preparation of synthetic derivatives. Accordingly, two new syntheses of tiacumicin B aglycone [ 163 , 164 ], the total synthesis of tiacumicin A [ 165 ], the total synthesis of tiacumicin B [ 166 ], and two reviews on tiacumicin B [ 144 , 145 ] were reported between 2017 and 2020.…”
Section: Antibiotics From Actinomycetes : From Isolation To Chemical Characterization Total Synthesis and Industrial Pmentioning
confidence: 99%
“…Fidaxomicin (1, tiacumicin B, lipiarmycin A3) constitutes a glycosylated macrocyclic lactone first discovered in 1972 in a culture of Actinoplanes deccanensis [1][2][3] and later re-isolated several times over the years. [4][5][6][7][8][9][10][11] This complex natural product has been introduced in the clinic and was reported to display superior properties compared to vancomycin and metronidazole. [12] Fidaxomicin shows a narrower spectrum of activity and it is particularly active against C. difficile, allowing the normal gut flora to recover.…”
Section: Introductionmentioning
confidence: 99%
“…Fidaxomicin (1, tiacumicin B, lipiarmycin A3) constitutes a glycosylated macrocyclic lactone first discovered in 1972 in a culture of A. deccanensis [1][2][3] and later re-isolated several times over the years. [4][5][6][7][8][9][10][11] This complex natural product has been introduced in the clinic and was reported to display superior properties compared to vancomycin and metronidazole. [12] Fidaxomicin shows a narrower spectrum of activity and it is particularly active against C. difficile, allowing the normal gut flora to recover.…”
Section: Introductionmentioning
confidence: 99%